Desenvolvimento e implementação de uma técnica de projeto e de controle de inversor conectado à rede elétrica com filtro LCL saturável - Tibúrcio, Silas Allyson Souza (2017)
Renewable energy sources controlled by electronic power converters are part of the electric power matrix in many countries. The nonlinear nature of electronic converters requires the use of filters at the interface with the electric power systems to mitigate the distortion of the injected current. Usually, the design of the control system and the design of the filter are disconnected one from the other, making difficult to optimize the two designs. This work proposes a new design procedure for an LCL filter topology that takes into account also the optimization of the current control algorithm in terms of both robustness and dynamic performances. The proposed approach considers also parameter variations that are usually neglected by the most common methodologies, such as, magnetic permeability variation of commercial cores due to saturation phenomena that causes significant variation of the inductances depending of the instantaneous value of the current that is flowing through the inductance. More specifically, based on the analysis of the LCL filter equations, a design methodology that integrates the design of the inductance of the filter with the design of a feed-forward controller was developed. In this way, it was possible to minimize the complexity of the feed-forward controller on the basis of measurable parameter of the filter, and to prevent the use of complex controller for the current control loop. In fact, the use of a simple Proportional Integral controller in the current control loop produces low steady state error and allows the use of standard techniques for the design of the controller parameters. Additionally, a method for the active damping of the filter was designed on the basis of the virtual resistance concept. Results of simulation and experimental tests demonstrated the effectiveness of the proposed control system and fulfillment of the requirements established in the LCL filter design. The test bench was comprised of a 15 [kW] three-phase inverter, a DS1103 PPC/dSPACE board and nominal inductances of 910 [μH], 597 [μH], and capacitors of 1.5 [μF] delta-connected.